India's economic development since 1947 - Kapila, Uma. (New Delhi Academic Foundation, 2007)
Contributed articles.
"Previously entitled Indian economy since independence".
Keywords: India -- Economic policy -- 1947-.; India -- Economic conditions -- 1947-.